THE ECONOMIC VALUE AND FEASIBILITY ANALYSIS OF MAGGOT CULTIVATION AS A BIOCONVERSION OF ORGANIC WASTE - Suwadji, Lantip Susilowati; Bachtiar, Jusuf; Sarinastiti, Anugerah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Organic waste is a fairly high problem when compared to other waste problems. Efforts to reduce organic waste are carried out by managing organic waste using biological bioconversion techniques which involve microorganisms to convert the waste into high-value products with the help of maggots or Black Soldier Fly (BSF) in the BSF Nusantara Tulungagung maggot cultivation business. This research aims to examine (1) the economic value of the BSF Nusantara Tulungagung maggot cultivation business using BEP analysis, (2) the level of feasibility of the BSF Nusantara Tulungagung maggot cultivation business using Gross B/C, (3) Analysis of the economic value and feasibility of the BSF maggot cultivation business Tulungagung Archipelago. The method uses descriptive quantitative. The source of data obtained is primary data in the form of financial data for BSF Nusantara Tulungagung in 2023 which includes income, production costs, selling prices and other costs related to the maggot cultivation business and secondary data in the form of previous research related to the research title and data resulting from the researcher's analysis . The research results show that the calculation of economic value using the Rupiah BEP is IDR 33,997,919. Meanwhile, the BEP for the wet maggot production unit is 1,527.87 kg and the BEP for the dry maggot production unit is 556.09 kg. Calculation of the feasibility level using Gross B/C shows an end point of 1.15. So the BSF Nusantara Tulungagung maggot cultivation business has economic value and is worthy of development.